Cytopathological Analysis of Cyst Fluid Enhances Diagnostic Accuracy of Mucinous Pancreatic Cystic Neoplasms. Issue 24 (June 2015) - Utomo, Wesley K.; Braat, Henri; Bruno, Marco J.; van Eijck, Casper H.J.; Koerkamp, Bas Groot; Krak, Nanda C.; van de Vreede, Adriaan; Fuhler, Gwenny M.; Peppelenbosch, Maikel P.; Biermann, Katharina; Li., Jianfeng
<x xml:space="preserve">Abstract</x> Abstract Widespread use of cross-sectional imaging and increasing age of the general population has increased the number of detected pancreatic cystic lesions. However, several pathological entities with a variety in malignant potential have to be discriminated to allow clinical decision making. Discrimination between mucinous pancreatic cystic neoplasms (PCNs) and nonmucinous pancreatic lesions is the primary step in the clinical work-up, as malignant transformation is mostly associated with mucinous PCN. We performed a retrospective analysis of all resected PCN in our tertiary center from 2000 to 2014, to evaluate preoperative diagnostic performance and the results of implementation of the consensus guidelines over time. This was followed by a prospective cohort study of patients with an undefined pancreatic cyst, where the added value of cytopathological mucin evaluation to carcinoembryonic antigen (CEA) in cyst fluid for the discrimination of mucinous PCN and nonmucinous cysts was investigated. Retrospective analysis showed 115 patients operated for a PCN, with a correct preoperative classification in 96.2% of the patients. High-grade dysplasia or invasive carcinoma was observed in only 32.3% of mucinous PCN. In our prospective cohort (n = 71), 57.7% of patients were classified as having a mucinous PCN. CEA ≥192 ng/mL had an accuracy of 63.4%, and cytopathological mucin evaluation an accuracy of 73.0%. Combining these 2 tests further improved diagnostic accuracy of a mucinous PCN to 76.8%. CEA level and mucin evaluation were not predictive of the degree of dysplasia. These findings show that adding cytopathology to cyst fluid biochemistry improves discrimination between mucinous PCN and nonmucinous cysts.